Anemia prevention attitudes and behaviour as determinants of anemia status in deaf adolescent girls - Zannah, Aflah Raudhotul; Heru Subaris Kasjono; Kurniati, Ana; Sujiyatini, Sujiyatini (Jurnal Kesehatan Ibu dan Anak, 2024)
Anemia remains a major nutritional problem among adolescents, especially girls, due to physiological changes and inadequate dietary intake. Deaf adolescents are particularly vulnerable due to limited access to health information, yet few studies have examined the role of attitude and behavior in this population.This study was to determine the relationship between attitudes and behaviors toward anemia prevention and anemia status among deaf adolescent girls. A cross-sectional analytical study was conducted at Public Special Needs School 1 Bantul, Yogyakarta, Indonesia involving 28 deaf adolescent girls aged 10–19 years using total sampling. Data were collected through validated questionnaires assessing attitudes and behaviors toward anemia (Cronbach’s Alpha: 0.746 and 0.827, respectively). Hemoglobin levels were measured using the EasyTouch GCHb device. Data were analyzed using Spearman Rho correlation with a significance level of p < 0.05. A strong positive correlation was found between attitudes and anemia status (r = 0.681, p = 0.000) and between behavior and anemia status (r = 0.708, p = 0.000). Most anemic participants had poor behavioral scores and came from low-income families. Additionally, all anemic participants had begun menstruating, suggesting physiological and socioeconomic risk factors. Attitudes and behaviors are significantly associated with anemia status among deaf adolescent girls. Despite having positive attitudes, environmental and socioeconomic barriers may hinder healthy behavior implementation. Tailored and accessible health education, alongside cross-sectoral interventions, is needed to reduce anemia prevalence in adolescents with disabilities.